AN ADAPTIVE HARMONIC COMPENSATION STRATEGY FOR THREE-PHASE SHUNT ACTIVE POWER FILTER BASED ON DOUBLE SECOND-ORDER GENERALIZED INTEGRATOR WITH PREFILTER - S. Kalkoul (National Technical University "Kharkiv Polytechnic Institute", 2020)
Abstract. This study presents a straightforward adaptive prefiltering algorithm based on a double second-order generalized integrator with prefilter to solve one of the power quality issues, this algorithm is in charge of the determination of the reference harmonic currents in the control of three-phase shunt active power filter which presents an effective way to enhance the grid current quality. The proposed algorithm is used twice, to extract the harmonic currents produced by the non-linear loads and be an interesting part in the estimation of the frequency and amplitude of the fundamental voltage in various anomalies which can be noticed on the grid voltage. The performance, precision, and robustness of the proposed method are evidenced under balanced, unbalanced, and distorted grid voltage in the simulation and experimental results obtained by the implementation of the shunt active power filter on MATLAB-Simulink environment and the dSPACE 1104 platform respectively.